Inventário de emissões atmosféricas de MP2,5 e BC oriundas da combustão em Londrina, Paraná - Fandiño, Isabella Charres (2019)
Atmospheric emission inventories play a pivotal role in air quality management since they allow the identification of the main emission sources and the main pollutants that affect the air quality to further estimate the magnitude of their emissions. In addition, inventories provide input data for dispersion. In Brazil, emissions inventories are focused mainly in the transport sector and some air pollutants at national, state and regional levels. However, there is a lack of studies on emission estimates of fine particulate matter (PM2.5) and black carbon (BC), especially at the municipal level. This research developed the first inventory of PM2.5 and BC emissions for the municipality of Londrina - PR, using the emission factor method and combining top-down and bottom-up approaches for the base year 2018. This inventory comprises the emissions from the industrial and commercial sector: by burning biomass and fossil fuels in industries, pizzerias, steakhouses and bakeries and road transport, and in the waste sector, by burning solid urban waste (SUW). The calculation of emissions was based on official data, emission factors (EF) proposed by the European Environment Agency (EEA) and scientific research, and the application of questionnaires on fuel consumption in the commercial sector. Uncertainty was also quantified using the error propagation method following the methodology of the Intergovernmental Panel on Climate Change (IPCC). Total emissions were estimated as 418 t of MP2,5 and 66 t of BC. The open burning of SUW is the dominant source of PM2.5, accounting for 56% of total emissions. BC emissions are strongly related to industrial processes, road transport, SUW burning and commercial establishments that contributed to 40%, 31%, 22% and 6% on the total emission, respectively. The uncertainties in industrial emissions were quantified as ± 115% for PM2.5 and ± 281% for BC. The uncertainties in PM2.5 and BC emissions from the commercial sector were ±80% and ±182% respectively. Furthermore, it was observed that emissions calculated from different sets of EF varied widely. These differences may be associated with the measurement method and the local conditions where the EF were estimated. Finally, to improve this inventory and guide the development of inventories in other Brazilian cities, it is recommended to compile detailed EF representative of the local conditions in which the inventory is intended to be compiled. It was found that the EF published by the EEA can have limitations when used in developing countries, since technologies may differ greatly from those used in developed countries. Moreover, emission sources, such as domestic biomass combustion and SUW open burning are not compiled in that guide.